Building Partnerships with Families and Communities: A Case Study - Dhian Gowinda Luh Safitri (Universitas Negeri Semarang, 2023)
This case study aims to explore the challenges and benefits of school-family-community partnerships in early childhood education in Indonesia. The purpose of the study is to illustrate how the Indonesian Partnership framework can be used to build, evaluate and address the challenges of such partnerships. The method used is a case study approach, which examines a specific early childhood education setting. The study found that the Indonesian Partnership framework can help schools structure and initiate partnership programs, as well as evaluate and sustain the activities. The study also highlights the importance of reflection and evaluation in collaboration. The results suggest that teacher training programs on building partnerships with families and communities could equip teachers with communication skills, strategies to address challenges, and knowledge to evaluate and sustain partnership programs.